2007
DOI: 10.1021/ja0724700
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Encapsulation in a Silicon Clathrate Type I Structure:  Na5.5(H2)2.15Si46:  Synthesis and Characterization

Abstract: A hydrogen-encapsulated inorganic clathrate, which is stable at ambient temperature and pressure, has been prepared in high yield. Na5.5(H2)2.15Si46 is a sodium-deficient, hydrogen-encapsulated, type I silicon clathrate. It was prepared by the reaction between NaSi and NH4Br under dynamic vacuum at 300 degrees C. The Rietveld refinement of the powder X-ray diffraction data is consistent with the clathrate type I structure. The type I clathrate structure has two types of cages where the guest species, in this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 38 publications
3
60
2
1
Order By: Relevance
“…From this plot, it can be seen that a number of materials fall close to the gravimetric and temperature ranges considered necessary for vehicular applications. Others, such as silicon nanoparticles [58][59][60][61] release hydrogen at too high a temperature, and do not release hydrogen with adequate gravimetric capacity. When the CHSCoE concluded its research, chemical regeneration of spent fuel from ammonia borane had been demonstrated in the laboratory with two major variants with over ten regeneration schemes having been partially or completely demonstrated, thereby showing potential to overcome regeneration as a barrier to the technological implementation of chemical hydrogen storage; however, more R&D is need to reduce cost and increase efficiencies.…”
Section: Hydrogen Storage Research In the Doe Chemical Hydrogen mentioning
confidence: 99%
“…From this plot, it can be seen that a number of materials fall close to the gravimetric and temperature ranges considered necessary for vehicular applications. Others, such as silicon nanoparticles [58][59][60][61] release hydrogen at too high a temperature, and do not release hydrogen with adequate gravimetric capacity. When the CHSCoE concluded its research, chemical regeneration of spent fuel from ammonia borane had been demonstrated in the laboratory with two major variants with over ten regeneration schemes having been partially or completely demonstrated, thereby showing potential to overcome regeneration as a barrier to the technological implementation of chemical hydrogen storage; however, more R&D is need to reduce cost and increase efficiencies.…”
Section: Hydrogen Storage Research In the Doe Chemical Hydrogen mentioning
confidence: 99%
“…[51] The synthesis was carried out by reacting NaSi and NH 4 Br under dynamic vacuum at 300 °C. Similarly to Na 5.5 (H 2 ) 2.15 Si 46 , the noble gas atoms could also coexist in a clathrate structure with other types of guest atoms such as alkali metals.…”
Section: Resultsmentioning
confidence: 99%
“…There are two seminal papers from this work just published in peer-recognized journals at the end of 2007. The first is on Ca(NH 2 BH 3 ) 2 4 . The second regards LiNH 2 BH 3 and NaNH 2 BH 3 materials 5 .…”
Section: Current Statusmentioning
confidence: 99%